2012
DOI: 10.5772/50338
|View full text |Cite
|
Sign up to set email alerts
|

Dual Drug Release of Triamterene and Aminophylline from Poly (N-Isopropylacrylamide) Hydrogels

Abstract: We used temperature-sensitive poly(Nisopropylacrylamide) hydrogels as drug delivery systems, so changes in body temperature induced by pathogens could act like external stimuli to activate controlled release of the drugs incorporated in the hydrogel. In the distilled water combined release studies, we chose two model drugs: aminophylline and triamterene. The amount of drug released was measured by UV-Vis spectroscopy following the evolution of the absorption peaks of aminophylline (271 nm) and triamterene (365… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The different release mechanisms for curcumin and the 4‐aminoquinoline analog suggest that the hydrogel has a marked influence on their release behavior of the drugs when used in combined delivery. Similar release pattern of two drugs from dual‐drug delivery systems have been reported by Castro et al on dual‐drug release of triamterene and aminophylline from poly ( N ‐isopropylacrylamide) hydrogels and Wei et al on dual‐drug release study of doxorubicin and aspirin from hydrogel composites . Pearale et al reported similar finding which involved a combination of fast diffusion controlled kinetics for smaller molecules together with a slow diffusion‐controlled kinetics for bigger molecules from a multidrug delivery hydrogel system for spinal cord injury repair …”
Section: Resultssupporting
confidence: 72%
“…The different release mechanisms for curcumin and the 4‐aminoquinoline analog suggest that the hydrogel has a marked influence on their release behavior of the drugs when used in combined delivery. Similar release pattern of two drugs from dual‐drug delivery systems have been reported by Castro et al on dual‐drug release of triamterene and aminophylline from poly ( N ‐isopropylacrylamide) hydrogels and Wei et al on dual‐drug release study of doxorubicin and aspirin from hydrogel composites . Pearale et al reported similar finding which involved a combination of fast diffusion controlled kinetics for smaller molecules together with a slow diffusion‐controlled kinetics for bigger molecules from a multidrug delivery hydrogel system for spinal cord injury repair …”
Section: Resultssupporting
confidence: 72%
“…Thus, these studies clearly demonstrate that using different methods of binding drug molecule to the biopolymer through interaction with TiO 2 provide slow release, and most importantly, the level of released drug remains constant over a long time. The observed difference between release times of DS and PCA-D can be also explained by different solubility of drugs in water 52,53 . Specifically, the solubility of Diclofenac sodium 54 at 25 ºC is 50 mg/ml, which is higher than that of Penicillamine D (30 mg/ml).…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…The incorporation of two or more different drugs into the same hydrogel structure can decrease its properties and exhibit a very challenging behavior . The combination of various drugs with different therapeutic effects has gathered much interest recently, since it can potentially treat infections and accelerate the tissue healing process.…”
Section: Introductionmentioning
confidence: 99%